# Calculator search results

Formula
Solve the equation
Graph
$y = \dfrac { x } { 4 } - 1$
$y = \dfrac { x } { 3 } + 1$
$x$-intercept
$\left ( 4 , 0 \right )$
$y$-intercept
$\left ( 0 , - 1 \right )$
$x$-intercept
$\left ( - 3 , 0 \right )$
$y$-intercept
$\left ( 0 , 1 \right )$
$\dfrac{ x }{ 4 } -1 = \dfrac{ x }{ 3 } +1$
$x = - 24$
 Solve a solution to $x$
$\color{#FF6800}{ \dfrac { x } { 4 } } \color{#FF6800}{ - } \color{#FF6800}{ 1 } = \color{#FF6800}{ \dfrac { x } { 3 } } \color{#FF6800}{ + } \color{#FF6800}{ 1 }$
 Multiply both sides by the least common multiple for the denominators to eliminate the fraction 
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 12 } = \color{#FF6800}{ 4 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 12 }$
$3 x - 12 = \color{#FF6800}{ 4 } \color{#FF6800}{ x } + 12$
 Move the variable to the left-hand side and change the symbol 
$3 x - 12 \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ x } = 12$
$3 x \color{#FF6800}{ - } \color{#FF6800}{ 12 } - 4 x = 12$
 Move the constant to the right side and change the sign 
$3 x - 4 x = 12 \color{#FF6800}{ + } \color{#FF6800}{ 12 }$
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ x } = 12 + 12$
 Organize the expression 
$\color{#FF6800}{ - } \color{#FF6800}{ x } = 12 + 12$
$- x = \color{#FF6800}{ 12 } \color{#FF6800}{ + } \color{#FF6800}{ 12 }$
 Add $12$ and $12$
$- x = \color{#FF6800}{ 24 }$
$\color{#FF6800}{ - } \color{#FF6800}{ x } = \color{#FF6800}{ 24 }$
 Change the sign of both sides of the equation 
$\color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 24 }$
 그래프 보기 
Graph
Solution search results
Have you found the solution you wanted?
Try again
Try more features at QANDA!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture